An Ontology-Based Transformation Model for the Digital Forensics Domain - Grigaliunas, Sarunas; Toldinas, Jevgenijus; Venckauskas, Algimantas (Elektronika ir Elektrotechnika, 2017)
The creation of an ontology makes it possible to form common information structures, to reuse knowledge, to make assumptions within a domain and to analyse every piece of knowledge. In this paper, we aim to create an ontology-based transformation model and a framework to develop an ontology-based transformation system in the digital forensics domain. We describe the architecture of the ontology-based transformation system and its components for assisting computer forensics experts in the appropriate selection of tools for digital evidence investigation. We consider the use of the attributes of Extensible Markup Language document transformation to map the computer forensics ontology and we use the representations in the National Institute of Standards and Technology’s “Computer Forensics Tool Catalog” for aligning one form with the other.DOI: http://dx.doi.org/10.5755/j01.eie.23.3.18337